Developing an Islamic corporate culture - Fontaine, Rodrigue Ancelot Harvey (Springer, 2022)
This chapter looks at how an organization can develop an Islamic corporate culture. It summarises some of the work done in this area since 2010. It explores the role of regular training workshops. To illustrate how this might work in practice, the outline of a workshop based on surah al-An'am is presented.